Rantai Nilai Pemasaran Telur Itik di Sentra Peternakan Itik, Kecamatan Gadingrejo, Kabupaten Pringsewu - Maria Herawati; Sari Setiyowati (Wahana Peternakan, 2020)
This research aims to find out the marketing value chain of duck egg in the central farm of duck in Gadingrejo District, Pringsewu Regency, Lampung. The result showed that the highest increase in value added occurs in the farmer because the farmer carry out processing in addition to selling in the form of consumption eggs processing into processed eggs or breeding. Keywords: Duck, egg, marketing, value chain, value added